Carboxylic ionophores enhance the cytotoxic potency of ligand- and antibody-delivered ricin A chain (The Rockefeller University Press, 1984)
The highly selective cytotoxicity of site-directed ricin A chain conjugates can be potentiated by membrane-active carboxylic ionophores. The combined use of the two agents results in much faster inactivation of ribosomes and subsequent cell death and lysis. The potency of A chain cytotoxins is correspondingly increased by several orders of magnitude and cells that sparsely express the target antigen or receptor can be killed.